2015
DOI: 10.1021/acs.inorgchem.5b01202
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photodissociation of Acetonitrile Ligands in Ruthenium Polypyridyl Complexes Studied by Density Functional Theory

Abstract: Metal complexes that release ligands upon photoexcitation are important tools for biological research and show great potential as highly specific therapeutics. Upon excitation with visible light, [Ru(TQA)(MeCN)2]2+ [TQA = tris(2-quinolinylmethyl)amine] exchanges one of the two acetonitriles (MeCNs), whereas [Ru(DPAbpy)MeCN]2+ [DPAbpy = N-(2,2′-bipyridin-6-yl)-N,N-bis(pyridin-2-ylmethyl)amine] does not release MeCN. Furthermore, [Ru-(TQA)(MeCN)2]2+ is highly selective for release of the MeCN that is perpendicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 63 publications
5
47
0
Order By: Relevance
“…Loss of CH 3 CN from N6 leads to 3 MC 1 , a trigonal bipyramidal complex (with N3–Ru–N1 as the axis) that is 5 kcal/mol more stable than the loss of CH 3 CN from N1 which forms 3 MC 2 , a square pyramidal structure (with Ru–N3 as the axis). 28 These results are in good agreement with previous observations, 25 which showed that photochemical dissociation of the N6 CH 3 CN is significantly more facile than the N1 CH 3 CN for Ru-quinoline and Ru-bipyridine complexes. 28 The N6 CH 3 CN was found to be more labile than the N1 CH 3 CN in the triplet excited states because of a favorable orbital mixing between the aromatic ligand π * and the Ru d σ * orbitals that characterize the Ru–N6 CH 3 CN dissociation.…”
Section: Computational Chemistrysupporting
confidence: 92%
See 1 more Smart Citation
“…Loss of CH 3 CN from N6 leads to 3 MC 1 , a trigonal bipyramidal complex (with N3–Ru–N1 as the axis) that is 5 kcal/mol more stable than the loss of CH 3 CN from N1 which forms 3 MC 2 , a square pyramidal structure (with Ru–N3 as the axis). 28 These results are in good agreement with previous observations, 25 which showed that photochemical dissociation of the N6 CH 3 CN is significantly more facile than the N1 CH 3 CN for Ru-quinoline and Ru-bipyridine complexes. 28 The N6 CH 3 CN was found to be more labile than the N1 CH 3 CN in the triplet excited states because of a favorable orbital mixing between the aromatic ligand π * and the Ru d σ * orbitals that characterize the Ru–N6 CH 3 CN dissociation.…”
Section: Computational Chemistrysupporting
confidence: 92%
“…6,7 Metal complexes also bind to functional groups that cannot be caged with organic fragments, including nitrogen-containing heterocycles, 815 thioethers 1618 and nitriles. 1928 Thus, metal complexes offer an orthogonal approach to organic caging methods.…”
Section: Introductionmentioning
confidence: 99%
“…58 Calculations provided an explanation for the increase and selectivity of ligand exchange, showing the presence of favorable orbital overlap in the excited state between the coplanar quinoline arms of the TQA ligand and the photolabile CH 3 CN ligand that is not present in the TPA complex. 59 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is generally accepted that ligands coordinated to the metal center can be easily dissociated upon irradiation with light at room temperature through population of the 3LF state(s). 27,33,43 In addition, caged molecules are released as a primary photochemical step, thus avoiding undesirable photo-damage that commonly occurs from organic photocages arising from dark reactions. 1,4346 The three-dimensional geometry and tunable photophysical properties also make Ru(II) polypyridyl complexes attractive photocaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…27,33,43 In addition, caged molecules are released as a primary photochemical step, thus avoiding undesirable photo-damage that commonly occurs from organic photocages arising from dark reactions. 1,4346 The three-dimensional geometry and tunable photophysical properties also make Ru(II) polypyridyl complexes attractive photocaging agents. 27,4648 …”
Section: Introductionmentioning
confidence: 99%